Gambaran Tindakan Pencegahan Penularan Covid-19 pada Pasien Hemodialisis di Rsud Arifin Achmad Provinsi Riau - Bayhakki; Dini Haryati Ulfa; Hellena Deli (STIKes Payung Negeri Pekanbaru, 2021)
Corona virus disease 2019 (Covid-19) is an infectious disease that infects the respiratory tract. Patients chronic kidney disease who undergoing hemodialysis are high risk of infections, patients who undergoing hemodialysis must take preventive every day. This study aims to Description of actions to prevent transmission of covid-19 in hemodialysis patients at Arifin Achmad Hospital, Riau Province. The research design used is descriptive with a quantitative approach. The sampling method used was the Consecutive Sampling method, with a total sample of 43 respondents according to the inclusion criteria, namely willing to be respondents and patients undergoing hemodialysis. The results showed the majority of research respondents aged 56-65 years as much as 46.5%, male gender as much as 60.5% and high school education as much as 37.2%. The results of actions to prevent the transmission of covid-19 in hemodialysis patients in the